El trato discriminatorio de la filiación extramatrimonial en Marruecos - Adnane, Abdelhamid (Revista de Derecho Político, 2013)
No hay ninguna disposición de rango constitucional que pueda legítimamente fundamentar un trato desigualitario entre hijos nacidos de un matrimonio legítimo y los nacidos a raíz de una relación extramatrimonial. Los derechos de los hijos son cuestiones integrantes de los conceptos de orden público e interés social, prevalentes ante cualquier derecho individual del progenitor. There is no disposition of constitutional range that could base legitimately a not egalitarian treatment between born children of a legitimate marriage and born immediately after an extramarital relation. The rights of the children are integral questions of the concepts of public order and social interest, which must prevail before any individual right of the progenitor.